Building the case for a trans-Afghan gas corridor - Bochkarev, D (Oxford Institute for Energy Studies, 2012)
Natural gas has a potential to gain importance in India and Pakistan as a key component of the energy mix, particularly in the power sector. Gas is already playing a major role in Pakistan’s energy sector and is rapidly gaining market share in India. For example, Pakistan has the region’s highest per capita natural gas consumption with the notable exceptions of gas-rich Iran and Turkmenistan.